(untitled) (Stamford Journal of Microbiology, 2022)
Starch degrading bacteria are vital for various industries like food, fermentation, textile, and paper. The aim of this study is to isolate and characterize bacteria able to degrade starch from the rhizosphere of soil located in Mymensingh, Bangladesh. Collected soil sample was serially diluted in sterilized peptone water, poured on sterilized starch agar plates and incubated at 37ºC for 24 hours. The representative colonies showing different morphology was randomly picked up using the streaking method on nutrient agar media. A total of 8 bacterial colonies were isolated and labelled as MSH 01, MSH 02, MSH 03, MSH 04, MSH 05, MSH 06, MSH 07, and MSH 08. Biochemical characteristics showed that all the isolates belonged to the genera Bacillus. Among those, MSH 06 showed the highest starch degrading index (SDI) followed by MSH 02 and MSH 05. Surveillance to identify microbial species with enhanced starch hydrolyzing potential might be helpful in biotechnology industries. Stamford Journal of Microbiology, Vol.12 (1) 2022: 21-24